Interleukin-18 and Gamma Interferon Production by Oral Epithelial Cells in Response to Exposure to Candida albicans or Lipopolysaccharide Stimulation - Rouabhia, Mahmoud (American Society for Microbiology, 2002)
Oral candidiasis is a collective name for a group of disorders caused by the dimorphic fungus Candida albicans. Host defenses against C. albicans essentially fall into two categories: specific immune mechanisms and local oral mucosal epithelial cell defenses. Since oral epithelial cells secrete a variety of cytokines and chemokines in response to oral microorganisms and since C. albicans is closely associated with oral epithelial cells as a commensal organism, we wanted to determine whether interleukin-18 (IL-18) and gamma interferon (IFN-γ) were produced by oral epithelial cells in response to C. albicans infection and lipopolysaccharide (LPS) stimulation. Our results showed that IL-18 mRNA and protein were constitutively expressed by oral epithelial cells and were down-regulated by Candida infections but increased following LPS stimulation. Both C. albicans and LPS significantly decreased pro-IL-18 (24 kDa) levels and increased active IL-18 (18 kDa) levels. This effect was IL-1β-converting-enzyme dependent. The increase in active IL-18 protein levels promoted the production of IFN-γ by infected cells. No effect was obtained with LPS. Although produced only at an early stage, secreted IFN-γ seemed to be a preferential response by oral epithelial cells to C. albicans growth. These results provide additional evidence for the contribution of oral epithelial cells to local (direct contact) and systemic (IL-18 and IFN-γ production) defense against exogenous stimulation such as C. albicans infection or LPS stimulation.